Cultural beliefs on causes of cleft lip and/or palate and satisfaction of presurgical counselling : a multicenter study - Hussin, Ilyasak (2017)
Objective: To identify the cultural beliefs on causes of cleft lip among parents and caretakers of cleft patients in a multiracial and multiethnic background society of Malaysia. Methodology: A descriptive cross-sectional multicenter study involving parents/primary caretakers of cleft patients. They were interviewed with questions from an adapted proforma to elicit their cultural beliefs on the aetiology of cleft. At the same time their socioeconomic demographics, barriers encountered in receiving cleft treatment and level of satisfaction with pre-surgical counselling were also investigated. The study involved three centers providing cleft care from different regions of Malaysia. Results: There were 295 respondents from different ethnic groups and cultural back rounds;; Malays (58.3%), indigenous Sabah (30.5%), Chinese (7.1%), Indian (2.4%), and ethnics of indigenous Peninsular Malaysia and Sarawak (1.7%). Among the Malays, they mainly attribute the aetiology of cleft to God’s will, father went fishing and inheritance. As for the indigenous Sabah respondents, a wide range of beliefs are attributed towards cleft. This include antenatal trauma experienced by the mother, fruit picking, and carpentry. As for the Chinese, several acts by a pregnant mother including cleaning the drains, sewing and using scissors are implicated for the cause of cleft. However, 98.3% of the parents agreed that their cultural background does not prevent the treatment of cleft. Those from lower socioeconomic background and lower education background were more likely to encounter difficulties while receiving cleft treatment which include financial constraints and transportation. Even so, there is an overall high level of satisfaction with pre-surgical counselling for cleft patients.Conclusion: There is a wide range of cultural beliefs among the multiethnic society of Malaysia. It shows the colorful and diverse beliefs among parents of our cleft patients. Fortunately, these beliefs do not prevent them from seeking and continuing treatment for their children. The difficulties while receiving cleft treatment were mainly of financial constraints and transportation, which were more likely to be encountered by those from lower income and lower education background. In spite of this, the level of satisfaction with pre-surgical counselling is high.